EFFECT OF SERUM ANTIOXIDANTS (VITAMIN E, C AND A) IN LUNG CANCER PATIENTS - Rahman, MD. Mustafizur; Islam, Sheikh Nazrul (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Intake of vitamin E, C and A have been reported to reduce lung cancer risk because of their roles as regulators of cell differentiation (vitamin A), antioxidants (vitamins C and E), and modulators of DNA synthesis, methylation and repair. Some case-control studies have found inverse associations between intakes of these vitamins and lung cancer risk. However, most of the prospective studies evaluating these nutrients have not found clear inverse associations. Because many of these prospective studies have included less than 100 lung cancer cases, they lacked statistical power to detect modest inverse associations. Therefore, in order to address the national issue the present study attempted a little beat to explore the association between some antioxidant vitamins with lung cancer. Methods: In this study we investigated cases (lung cancer) and control group (Smoker); serum Vitamin A, Vitamin C and Vitamin E level estimation were focused. Detailed information on these facts was collected by questionnaire and blood sample analysis, which were then complied and analyzed with a statistical software package. Results: In this study we found that Serum vitamin C levels were significantly higher in case (0.8 ± 0.2µg/dl) than in control (0.30±0.1µg/dl). But Serum vitamin A and serum vitamin E level showed less difference between cases (75.89±24.1µg/dl) and (657.25±322.7µg/dl) and controls (74.87±26.6µg/dl) and (641.55±413.5µg/dl) respectively. Conclusion: It can be suggested that vitamin E, C, and A has no effect on lung cancer patients.